HEALING MANTRAS OF BANJARESE AND THEIR PORTRAYAL OF SOCIO-CULTURAL VALUES - Ninuk Krismanti; Agustina Lestary; Jumainah Jumainah (Universitas Lambung Mangkurat, 2018)
This study is set as an attempt to study Banjarese healing mantras as part of oral literature that needs to be preserved. Mantras are now prone to loss because more and more people no longer believe in them. In this study, the healing mantras are collected through documentation and interview. In terms of documentation, there are three books related to Banjarese Mantras that we examine to collect the data. In terms of interview, the respondents are chosen using purposive sampling from three regencies in South Kalimantan. The interview in this study is semi-structured interview. The collected data are analyzed using Anthropolinguistics approach focusing on structures, functions, and socio-cultural values behind the healing mantras. The results of the study show that structurally Banjarese healing mantras are commonly opened and closed by Arabic words showing Islamic values. Seeing from their functions, Banjarese healing mantras are casted to heal 21 issues regarding to health. In relation to socio-cultural values, the Banjarese healing mantras show that nature and Islamic teaching play important role in Banjarese people’s lives.